1992
DOI: 10.1111/j.1476-5381.1992.tb13424.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory mechanisms in the passive cutaneous anaphylactic reaction in the rabbit: evidence that novel mediators are involved

Abstract: We have examined the mechanisms of local oedema formation in the passive cutaneous anaphylactic (PCA) reaction in the rabbit. IgE‐containing antiserum was injected i.d. and allowed to sensitize skin sites for periods up to 240 h. Antigen (bovine gamma globulin) was injected i.d. or i.v. and local oedema formation assessed by the accumulation of i.v. injected 125I‐labelled rabbit serum albumin. Potential inhibitors were mixed with antigen prior to i.d. injection or were administered i.v. Maximum oedema formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Goat anti-rabbit C5a antiserum was generated as described previously (32). Anti-rabbit IL-8 antiserum was generated in a similar manner by immunization of guineapigs with emulsions of synthetic rabbit IL-8 in Freund's complete and incomplete adjuvants injected subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…Goat anti-rabbit C5a antiserum was generated as described previously (32). Anti-rabbit IL-8 antiserum was generated in a similar manner by immunization of guineapigs with emulsions of synthetic rabbit IL-8 in Freund's complete and incomplete adjuvants injected subcutaneously.…”
Section: Methodsmentioning
confidence: 99%
“…The long duration of the PE response in this active cutaneous response (ACA) is in contrast to that for the passive cutaneous anaphylactic (PCA) response, which, when measured over 30 min was reported to have a half‐life of 15 min and to be almost complete by 60 min ( Hellewell et al ., 1992 ). This PCA response was also found to be dependent on prostaglandins (as determined by the use of indomethacin), but was not affected by H 1 receptor antagonists, platelet activating factor antagonists, 5‐lipoxygenase inhibitors, kallikrein inhibitors, bradykinin antagonists or an anti‐C5a antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the PE response to these two stimuli was further investigated using the microtubule inhibitor colchicine, which inactivated neutrophils. Hellewell et al . (1992) showed that intravenous injection of colchicine caused a slow decline in the total number of circulating leukocytes and in neutrophil number although colchicine causes a rapid inactivation of neutrophil chemotaxis through inhibition of microtubule activity.…”
Section: Discussionmentioning
confidence: 99%
“…Where possible, the effectiveness of the antagonist was demonstrated by inhibition of oedema induced by the agonist in the presence of a vasodilator dose of CGRP (see Brain & Williams, 1985). The dose of antagonist was chosen as follows: The histamine Hi receptor antagonist, mepyramine (3 nmol/site), and the PAF antagonist WEB2086 (100 nmol/site) were used at doses previously shown to inhibit effectively oedema induced by histamine (10 nmol/site) or PAF (1 nmol/site) respectively, in the presence of a vasodilator in rabbit skin (Hellewell et al, 1992). The bradykinin B2 receptor antagonist, Hoe 140, was used at a dose of 1 nmol/site, after preliminary experiments had indicated this to be an appropriate dose to inhibit oedema induced by bradykinin in rabbit skin.…”
Section: Effect Of Inhibitors Of Mediators Of Increased Microvascularmentioning
confidence: 99%
“…The cyclooxygenase inhibitor, indomethacin, which inhibits the conversion of arachidonic acid (AA) to vasodilator prostaglandins was used at a dose of 10 nmol/site which has been previously shown to abolish the potentiation of oedema induced by BK (0.1 nmol) when given together with AA (3 nmol) in rabbit skin (Hellewell et al, 1992). The nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester (L-NAME, 30 nmol) was used at a dose which has been previously shown to inhibit capsaicin-induced blood flow in rabbit skin .…”
Section: Measurement Of Skin Bloodflowmentioning
confidence: 99%